METODOLOGIAS DE COLETA, PRESERVAÇÃO E ARMAZENAMENTO DE AMOSTRAS DE ÁGUA PARA ANÁLISE DE MERCÚRIO - UMA REVISÃO - Kasper,Daniele (2015)
Knowing the mercury levels of an environment allows a diverse array of biogeochemical studies into the mercury cycle on a local or global scale. Among matrices commonly evaluated, water remains a challenge for research because its mercury levels can be very low, requiring development of complex analytical protocols. Currently, sample preservation methods, protocols that avoid contamination, and analytical techniques with low detection limits allow analysis of mercury in pristine waters. However, different protocols suggest different methods depending on a range of factors such as the characteristics of water sampled and storage time. In remote areas, such as oceanic and Amazonian regions, sample preservation and transport to a laboratory can be difficult, requiring processing of the water during the sampling expedition and the establishment of a field laboratory. Brazilian research on mercury in water can be limited due to difficulty obtaining reagents, lack of laboratory structure, qualified personnel, and financial support. Considering this complexity for analyzing water, we reviewed methodologies for sampling, preservation, and storage of water samples for analysis of the most commonly evaluated mercury species (dissolved gaseous mercury, reactive mercury, methylmercury and total mercury).